TRANSMISSION OF ANTIPLURALISM IN THE MILLENNIAL DIGITAL MEDIA SPACE - Shaleh, Shaleh; Ansyory, Anhar; Putro, Khamim Zarkasyih; Jandra, Mifedwil (UIN Raden Mas Said Surakarta, 2020)
Excessive religious attitudes have shown an increasing trend among young people in some research results. This research intends to examine the transmission of anti-pluralism in the digital media space of millennial youth. For this purpose, researchers used a qualitative case study method by collecting data through site observations used by millennials, searching for documents on digital media, and interviews with several youths, some of whom had been influenced by the doctrine of anti-pluralism. The results of this study indicated that adherents of anti-pluralism had transmitted this understanding in the digital space of millennials through hyperlinks between sites. These links are used to transform understandings, among others: anti-difference, sole ruler of truth, thaghut, anti-Pancasila, and revolution. This transmission was an effort to carry out clandestine regeneration with the young millennial generation who are the primary users of this media.